2016
DOI: 10.15252/embj.201593458
|View full text |Cite
|
Sign up to set email alerts
|

HSV ‐1 ICP 27 targets the TBK 1‐activated STING signalsome to inhibit virus‐induced type I IFN  expression

Abstract: Herpes simplex virus (HSV) 1 stimulates type I IFN expression through the cGAS-STING-TBK1 signaling axis. Macrophages have recently been proposed to be an essential source of IFN during viral infection. However, it is not known how HSV-1 inhibits IFN expression in this cell type. Here, we show that HSV-1 inhibits type I IFN induction through the cGAS-STING-TBK1 pathway in human macrophages, in a manner dependent on the conserved herpesvirus protein ICP27. This viral protein was expressed de novo in macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(114 citation statements)
references
References 63 publications
3
110
1
Order By: Relevance
“…Our previous study has demonstrated that VP24 inhibited the cGAS-STING-mediated IFN-␤ signaling pathway by blocking the interaction between TBK1 and IRF3 (37). In addition, a recent study by Christensen et al demonstrated that HSV-1 immediate early protein ICP27 interacted with TBK1 and STING and abrogated activation of IRF3 (38). Nevertheless, our current knowledge on the countermeasure of DNA viruses against the cGAS/STING-mediated DNA-sensing signal pathway is still limited, and no viral protein has been identified to act directly on cGAS.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous study has demonstrated that VP24 inhibited the cGAS-STING-mediated IFN-␤ signaling pathway by blocking the interaction between TBK1 and IRF3 (37). In addition, a recent study by Christensen et al demonstrated that HSV-1 immediate early protein ICP27 interacted with TBK1 and STING and abrogated activation of IRF3 (38). Nevertheless, our current knowledge on the countermeasure of DNA viruses against the cGAS/STING-mediated DNA-sensing signal pathway is still limited, and no viral protein has been identified to act directly on cGAS.…”
Section: Discussionmentioning
confidence: 95%
“…In this setting, the viral interferon-regulatory factor (vIRF1) of Kaposi’s sarcoma-associated herpesvirus (KSHV) inhibits STING phosphorylation and concomitant activation by preventing its interaction with TBK1 [28]. In addition, ICP27, a regulatory protein encoded by herpes simplex virus type 1, prevents the phosphorylation of IRF3 by interacting with STING and TBK1 [29]. Likewise, HPV E7 and Adenovirus E1A binds STING through a LXCXE motif and antagonizes DNA sensing in vitro [7], while E2 proteins of high risk HPV can also reduce STING expression and IFN-κ transcription in human keratinocytes [20].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that both the TLR3-TRIF and cGAS-STING pathways are involved in control of HSV1 infections. In further support of a role for the cGAS-STING pathway in control of HSV1, there are now reports of close to 10 HSV1-encoded proteins targeting this pathway (Christensen et al, 2016;Deschamps and Kalamvoki, 2017;Huang et al, 2018;Orzalli et al, 2012b;Su and Zheng, 2017;Verpooten et al, 2009;Wang et al, 2013b;Ye et al, 2017;Zhang et al, 2018). However, it remains unresolved how HSV1 evades the IFN-mediated immune response in the brain.…”
Section: Introductionmentioning
confidence: 99%